2011
DOI: 10.2319/010711-5.1
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of landmark identification in the jaw and teeth on 3-dimensional cone-beam computed tomography images

Abstract: Objective: To compare the reproducibility of landmark identification on three-dimensional (3D) conebeam computed tomography (CBCT) images between procedures based on traditional cephalometric definitions (procedure 1) and those tentatively proposed for 3D images (procedure 2). Materials and Methods: A phantom with embedded dried human skull was scanned using CBCT. The acquired volume data were transferred to a personal computer, and 3D images were reconstructed. Eighteen dentists plotted nine landmarks related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…An additional search with the same search equation, performed using Google Scholar, found 6 new articles. The final number of articles was 21 (Berco et al, 2009;Bholsithi et al, 2009;Fuyamada et al, 2011;Gribel et al, 2011;Hassan et al, 2009;Lagrav ere et al, 2009Lagrav ere et al, , 2010Ludlow et al, 2009;Medelnik et al, 2011;de Oliveira et al, 2009;Olszewski et al, 2007Olszewski et al, , 2008Olszewski et al, , 2010Olszewski et al, , 2013Oz et al, 2011;Periago et al, 2008;Schlicher et al, 2012;Titiz et al, 2012;Varghese et al, 2010;Zamora et al, 2012Zamora et al, , 2011). An assessment of the risk of bias revealed that none of the articles met the adopted criteria.…”
Section: Resultsmentioning
confidence: 99%
“…An additional search with the same search equation, performed using Google Scholar, found 6 new articles. The final number of articles was 21 (Berco et al, 2009;Bholsithi et al, 2009;Fuyamada et al, 2011;Gribel et al, 2011;Hassan et al, 2009;Lagrav ere et al, 2009Lagrav ere et al, , 2010Ludlow et al, 2009;Medelnik et al, 2011;de Oliveira et al, 2009;Olszewski et al, 2007Olszewski et al, , 2008Olszewski et al, , 2010Olszewski et al, , 2013Oz et al, 2011;Periago et al, 2008;Schlicher et al, 2012;Titiz et al, 2012;Varghese et al, 2010;Zamora et al, 2012Zamora et al, , 2011). An assessment of the risk of bias revealed that none of the articles met the adopted criteria.…”
Section: Resultsmentioning
confidence: 99%
“…21 In practice, locating landmarks by consulting 2D MPR images may take up too much time. Given the laborious process of locating landmarks in 3D, the time-benefit ratio of 3D analyses is likely to be lower than that of conventional 2D analyses.…”
Section: Discussionmentioning
confidence: 99%
“…One solution to this problem would be the use of tentative landmark definitions. Fuyamada et al [19] showed that using separate definitions of landmark locations on each axis significantly improved the selection accuracy. This method could also reduce the time required to implement any necessary corrections.…”
Section: Discussionmentioning
confidence: 99%